Textile education during the 2020 pandemic: experiences in US, South Africa and Germany - Chris Pastore; Yordan Kyosev; Ali-Akbar Fassihi; Becky Flax (Communications in Development and Assembling of Textile Products)
The Covid-19 pandemic has had a major impact on higher education across the world. In this paper we consider how textile education has been impacted and what approaches have been employed to maintain quality education and laboratory experience when traditional methods are not appropriate. This paper considers three different countries – United States, South Africa and Germany. Each has been affected in a different way, has a different sociological makeup, and has developed distinct solutions to the challenge. Methods related to HyFlex, flipped classrooms, and blending learning have been applied by all three institutions. Lectures have been presented as pre-recorded videos, synchronous video conferencing, and hybrid. Similarly, laboratory and studio experiences have been handled through pre-recorded video, guided “at home” experiments, and modified in-person experiences. This paper gives an overview of the laboratory and studio experiences, time spent in preparation, and reaction of the students to remedies. It also addresses best practices from each country in the three continents.